Mindful Eating and Mental Health in University Students of Temuco, Chile: a case study - Escamilla Garcés, Carolina Andrea; Sandoval Obando, Eduardo Enrique; Fuentes Vilugrón, Gerardo; Caamaño Navarrete, Felipe (Pensando Psicología, 2025)
The quality of life of university students is a growing concern in the educational field, due to the physical, emotional, and cultural demands that this period of life places on emerging adults. Therefore, the study aimed to understand the implications of mindful eating on the mental health of young people attending a private university in Temuco, Chile, to promote general well-being in the educational setting. Methodologically, a qualitative approach was used through an exploratory, cross-sectional, and non-experimental design. Specifically, a non-probability convenience sample was used, consisting of 17 participants (53% men and 47% women), with an average age of 22 years, attending a private university in Temuco, Chile. Regarding the data collection technique, semi-structured interviews were used to obtain detailed information about the interviewees’ experiences, opinions, motivations, and beliefs. The collected stories were subsequently subjected to content analysis using semantic, thematic, and repetition criteria using ATLAS.TI 22 software. The results revealed that, although students recognize the importance of nutrition in their development, they report a lack of knowledge regarding the meaning of conscious eating. It was also evident that the poor eating habits reported by participants are attributed to the lack of organization and personal time management available to young people in the university context.